Early Percutaneous Cholecystostomy in Severe Acute Cholecystitis Reduces the Complication Rate and Duration of Hospital Stay. Issue 27 (July 2015) - Chou, Chung-Kai; Lee, Kuei-Chuan; Chan, Che-Chang; Perng, Chin-Lin; Chen, Chun-Ku; Fang, Wen-Liang; Lin, Han-Chieh; Paik., Woo Hyun
<x xml:space="preserve">Abstract</x> Abstract The optimal timing of percutaneous cholecystostomy for severe acute cholecystitis is unclear. The aim of this study was to investigate the timing of percutaneous cholecystostomy and its relationship to clinical outcomes in patients with inoperable acute severe cholecystitis. From 2008 to 2010, 209 consecutive patients who were admitted to our hospital due to acute cholecystitis and were treated by percutaneous cholecystostomy were retrospectively reviewed. The time periods from symptom onset to when percutaneous cholecystostomy was performed and when patients were discharged were recorded. In the 209 patients, the median time period between symptom onset and percutaneous cholecystostomy was 23 hours (range, 3–95 hours). The early intervention group (⩽24 hours, n = 109) had a significantly lower procedure-related bleeding rate (0.0% vs 5.0%, P = 0.018) and shorter hospital stay (15.8 ± 12.9 vs 21.0 ± 17.5 days) as compared with the late intervention group (>24 hours, n = 100). Delayed percutaneous cholecystostomy was a significant independent factor for a longer hospital stay (odds ratio 3.03, P = 0.001). In inoperable patients with acute severe cholecystitis, early percutaneous cholecystostomy reduced hospital stay and procedure-related bleeding without increasing the mortality rate.